Effect of Incorporation of Plant Extracts into the Soil on Physicochemical, Biological, and Enzymatic Properties of Soil. Issue 12 (4th July 2021) - Sikri, Neha; Sharma, Jitender; Dalal, Sunita
ABSTRACT: Soil health refers to its functionality and ecological equilibrium. Different indicators of soil health include its physical, chemical, biological, and biochemical attributes. The present study was undertaken to check the stress generated on the addition of urea in five different soils, sampled from various regions of state Haryana. The change in pH and urease activity was observed on urea treated soil, fertilized with two potential urease inhibitory plant extracts, Cassia fistula and Phyllanthus niruri . Urea incorporation raised the pH and urease activity of all soil types. Plant extracts fertilization positively regulated both attributes of all soil samples. Although Cassia fistula possessed excellent in vitro urease inhibitory potential as compared to Phyllanthus niruri, but for soil health Phyllanthus niruri and formulation Cassia fistula + Phyllanthus niruri (10:90) proved significantly better.